Pyloric stenosis associated Crohn's disease responding to adalimumab therapy - Gaggar, Sameer (Baishideng Publishing Group Co., Limited, 2012)
Gastroduodenal Crohn’s disease (CD) is rare and the response to standard medical therapy is often poor. Anti-tumor necrosis factor therapy has revolutionised the treatment of CD. We present a patient with pyloric stenosis associated with CD which improved with Adalimumab therapy. We recommend considering anti-tumor necrosis factor therapy in symptomatic gastroduodenal CD.